Cystatin C: A new biochemical marker in livestock sector - Sahoo, Pravas Ranjan; Swain, Parthasarathi; Nayak, Sudhanshu Mohan; Kar, Debasish; Mishra, Smruti Ranjan (Journal of Advanced Veterinary and Animal Research, 2016)
The livestock sector contributes largely to the economy of India. Different systemic diseases like renal diseases, neurological and cardiovascular diseases cause huge loss in production and productive potential of livestock in India, which is considered as a major concern for both small and large ruminants. Early detection of diseseses is essential to combat the economic loss. An efficient biochemical marker can be developed which would provide more specific, sensitive and reliable measurement of functions of different organs. Determination of endogenous marker Cystatin C may fulfill the above need which can provide a detection platform not only for Kidney function but also for assaying other organs function. Cystatin C is a low molecular weight protein which is removed from the bloodstream by glomerular filtration in the kidneys. Thus, it may act as a potential biological tool in diagnosis of renal and other systemic diseases in livestock. This mini-review focuses on the Cystatin C and its clinical importance which can be extensively employed in the livestock sector. http://doi.org/10.5455/javar.2016.c156